Re-description of two spiny clam shrimps (Crustacea: Branchiopoda: Spinicaudata) of the Indian subcontinent from Daday de Dees’s collection at MNHN with new insights on the validity of Eulimnadia compressa (Baird, 1860) and Eulimnadia chaperi (Simon, 1886) - Padhye, Sameer M.; Rabet, Nicolas (Zootaxa, 2017)
We provide complete re-descriptions of a few Indian spinicaudatan clam shrimp species studied from the collection of Daday de Deés stored at the Muséum National d’Histoire Naturelle (MNHN), Paris. For Eocyzicus bouvieri Daday, 1913 and Leptestheria sarsi (Daday, 1923), we highlight taxonomical characters, like cercopod and telson not elaborated by Daday in his original descriptions. We also study Eulimnadia compressa (Baird, 1860) first described from Nagpur, India, and later collected from Angkor, Cambodia, by Daday. The original description of E. compressa is brief, based mostly on the carapace. The type material was not studied by Daday and is now lost. This species therefore should be considered as nomen dubium until a thorough reinvestigation becomes possible. In addition, precise examination of the egg morphology of the two populations of the supposed E. compressa stored at the MNHN shows that there are two different species designated under the same name. Based on the distinct differences observed between the eggs, we re-instate the species status of Eulimnadia chaperi (Simon, 1886) synonymized to E. compressa. We highlight the morphological similarity in eggs of Cambodian population of the supposed E. compressa and South American Eulimnadia magdalenensis Roessler, 1990 using populations from Brazil for comparison and suggest that E. compressa must be designated as the latter species.